Kajian Fiqih Berbasis Margin Murabahah dan Kaitannya Dengan Risiko Reputasi - Nasrul Amanu (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine how much the impact of reputation risk on Islamic Banks in BPRS Patriot Bekasi, to analyze the implementation of Murabahah in BPRS Patriot Bekasi and to find solutions in implementing Murabahah which is considered imperfect which can lead to reputation risk at BPRS Patriot Bekasi. The method used is through qualitative research by means of observation and distributing questionnaires to respondents in the customers of the Patriot Bekasi Islamic People's Financing Bank (BPRS). From these results, there were 22 respondents or 72.6% of 30 respondents stated that the risk impact was very large on BPRS Patriot Bekasi, while 8 respondents or 27.4% of the 30 respondents sampled stated no, that the risk impact was very large on BPRS. Patriot Bekasi. There are 30 respondents or 100% of the 30 respondents said yes, that the Patriot Bekasi Islamic Rural Bank (BPRS) has conducted an analysis of the implementation of the Murabahah contract according to the condition of the community or the customer, so that it is expected that there will be no default or default. There were 29 respondents or 96.7% of 30 respondents said yes, that the Patriot Bekasi Islamic Rural Bank (BPRS) has been looking for a solution in implementing Murabahah which is considered imperfect which could lead to reputational risk to customers. Keywords: Murabahah, reputation risk, BPRS PATRIOT BEKASI JEL Clasification: D23, G21, G32, F38